Analisis Spasial berdasarkan Indeks Getis Ord Data Laju Inflasi Tahunan di Pulau Sumatra - Yuni naomi Yenusi; Adi Setiawan; Lilik Linawati (Maranatha University Press, 2020)
This study discusses the analysis of year-on-year inflation data on the island of Sumatra using the Getis-Ord General G index and the Getis-Ord Gi* Index, which will be compared with the Bootstrap Method. And the Mann Withney Test for comparison of two time periods. The results showed that the highest average inflation was in Pangkal Pinang City by 5.82, and the lowest was in Banda Aceh City by 3.63. There is a significant difference in the median inflation rate from the cities of inflation on the island of Sumatra except in the cities of Banda Aceh, Palembang and Batam. With a significance level alpha = 5%, it is concluded that there are spatial cluster and spatial autocorrelation patterns in February 2014. Cities with high inflation value cluster with its neighbors are the city of Pangkal Pinang, and the low inflation value cluster is Banda Aceh. It means that a region is close to other regions has a similar level of inflation in terms of high and low at a certain time. In other words, commodities contributing to inflation between adjacent regions are interrelated. Keywords—Getis-Ord General G Index, Getis-Ord Gi* Indeks, Inflation, Spatial Autocorrelation, Spatial cluster.